Audit committee characteristics and sustainability disclosures: A meta-analytical perspective - Hafiz Muhammad Arslan; Muhammad Mubeen; Songsheng Chen; Khoula Naseer; Sibgha Yaseen (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2024)
This research examines the association between audit committee characteristics (e.g., audit committee presence, audit committee meetings, audit committee size, audit committee financial expertise, audit committee independence, and audit committee effectiveness) and sustainability disclosures by conducting a meta-analysis of 93 peer-reviewed studies. Meta-regression analyses were performed using Stata 18.0. This study intends to fill the literature gaps by including three potential moderators: financial reporting quality, the social progress index, and the world corporate governance index. The findings show that considering different country settings, audit committee characteristics are vital in determining sustainability disclosures regardless of geographical variances. However, the world corporate governance index indicates insignificant moderation. Additionally, high- ranked journal studies have shown positive and significant results compared to low ranked because of properly handling endogeneity. The findings are consistent with institutional, agency, and stakeholder theories, suggesting that audit committee characteristics help firms meet societal and stakeholder interests by promoting sustainability disclosures. In contrast, the findings challenge the resource dependence theory and indicate that the internal control mechanism, specifically the audit committee, has more impact on sustainability disclosures than external mechanisms.
Keywords: 330; Audit committee characteristics; sustainability disclosures meta-analysis; financial reporting quality; social progress index; world corporate governance index